Letak Bidang Longsor Lereng Candi Selogriy0- Kabupaten Magelang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Selogriyo temple is one of the tourism objects in Magelang region. In 1998 the temple collapsed by land slide or slope failure. The main reason is the drainage system and slope stability disturbance. In general, the surface of sliding gives the forms of circulary cylindrical failure surface and the cross section is curve failure. The research was conducted to investigate the position of potential curves of sliding where the shear strength is minimum. The investigation carried out by field tests. One of the test was a static penetration by a static penetrometer of 25 kN capacity. The result showed that the slope failure at the Selogriyo temple area was occurred by easy stages, and the final position of sliding curve between 5,60 â 6,20 m depth from the soil surface.